Perceptions of eco-labelling among the Swedish food sector - Larsson, Lina (2022)
Eco-labelling is a promising approach to promote sustainable consumption. Despite a growing concern for the environmental consequences of food production, the use of eco-labels has remained low. To date, a large body of literature has focused on consumer perspectives of eco-labelling, while research on the food industry’s perspective has remained scarce. This study starts to address this gap by analysing the diverse perceptions of eco-labelling among Swedish processors, retailers, and label organisations. The aim of this study is to identify the most critical challenges of eco-labelling and to understand in what form eco-labels can set incentives for the provision of ecosystem services within the agri-food production.